Dampak Penerapan Integrated Care for Older People dan Ina-FRAIL dalam Menurunkan Sindroma Kerapuhan pada Lansia - Putra, Mochamad Ramadhan Arista Pesat Eka; Permanasari, Vetty Yulianty (UI Scholars Hub, 2026)
Indonesia is facing a significant increase in its elderly population, requiring effective and sustainable integrated geriatric services, one of which is through the implementation of Integrated Care for Older People (ICOPE) to assess intrinsic capacity decline combined with the Ina-FRAIL questionnaire to measure frailty in the elderly. This study aims to assess the condition of frailty in older adults through the ICOPE approach in integrated geriatric services at Humana Prima Hospital in Bandung using a quantitative design with an experimental approach. The assessment was conducted using the ICOPE and Ina-FRAIL instruments to monitor intrinsic capacity and the level of frailty in older adults. The results showed a prevalence of frailty impairment (50%), mobility limitations (56%), decreased appetite (46%), visual impairment (56%), hearing impairment (23%), and loss of interest or symptoms of depression (73%), with significant differences between the control and intervention groups before and after the implementation of ICOPE, as well as a meaningful relationship between frailty levels and geriatric syndromes. In conclusion, the combination of ICOPE and Ina-FRAIL is effective in comprehensively detecting geriatric syndromes and frailty in the elderly, so it is recommended that its application be expanded to primary health care facilities through training of health workers and integration of clinical follow-up to improve the quality of life of the elderly.